Reinforcing Animal Conservation Ideology in Children’s Media through Cultivation Theory and Gestalt Principles - Sundah, Johanna Ratuwani; Ahmad, Hafiz Aziz (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
This study explores the significance of storytelling in children’s media as a means to reinforce conservation ideology, particularly regarding the protection of Indonesia’s endemic wildlife. By applying Cultivation Theory, a communication framework developed by George Gerbner that posits long-term media exposure can influence an individual's perceptions of social reality, this research emphasizes how early and consistent exposure to conservation-themed content can shape children’s environmental awareness and values. Children’s media, including storybooks, animated films, and television series, serve not only as entertainment but also as a powerful tool for education and character development. Through visual storytelling, messages related to animal protection, ecological balance, and social responsibility can be effectively communicated in ways that are engaging and emotionally resonant for young audiences. The analysis focuses on narrative structures and visual elements, such as character design, setting, color, and sequence, which contribute to a child’s understanding and retention of conservation messages. The study finds that consistent use of symbolic imagery and compelling narratives fosters emotional involvement, empathy toward wildlife, and a sense of personal responsibility in children. This emotional engagement, paired with repeated exposure to conservation themes, strengthens memory retention and encourages pro-environmental behavior. Furthermore, the combination of Cultivation Theory and visual storytelling, supported by psychological principles such as Gestalt theory, proves to be an effective educational strategy. It highlights the potential of children’s media to not only entertain but also to shape attitudes and ideologies that support environmental stewardship from an early age. Ultimately, this research underscores the vital role of storytelling in shaping a more ecologically conscious generation.